PID controller design for semi-active car suspension based on model from intelligent system identification - Hanafi, Dirman (2010)
This paper presents a new method to design a semiactive suspension system. A semi-active suspension is developed by installing a variable shock absorber parallel with the passive suspension system and controlled using PID controller. A high fidelity mathematical model for capturing the realistic dynamic of car passive suspension system for the basic element of the semi-active suspension system is determined using the intelligent system identification. The car passive suspension system is assumed to have NARX model. The result shows that the response of the semi-active suspension system can follow the input signal, it means the PID controller is successfully control the variable shock absorber in order eliminate the road surface disturbances effect to the car body.